Negative Modulation of the Metabotropic Glutamate Receptor Type 5 as a Potential Therapeutic Strategy in Obesity and Binge-Like Eating Behavior - Oliveira, Tadeu P. D.; Gonçalves, Bruno D. C.; Oliveira, Bruna S.; de Oliveira, Antonio Carlos P.; Reis, Helton J.; Ferreira, Claudia N.; Aguiar, Daniele C.; de Miranda, Aline S.; Ribeiro, Fabiola M.; Vieira, Erica M. L.; Palotás, András; Vieira, Luciene B. (Frontiers in Neuroscience, 2021)
Obesity is a multifactorial disease, which in turn contributes to the onset of comorbidities, such as diabetes and atherosclerosis. Moreover, there are only few options available for treating obesity and most current pharmacotherapy causes severe adverse effects, while offering minimal weight loss. Literature shows that metabotropic glutamate receptor 5 (mGluR5) modulates central reward pathways. Herein, we evaluated the effect of VU0409106, a negative allosteric modulator (NAM) of mGluR5 in regulating feeding and obesity parameters. Diet induced obese (DIO) C57BL/6 mice were 14 days treated with VU0409106 and food intake, body weight, inflammatory/hormonal levels and behavioral tests were performed. Our data suggest reduction of feeding, body weight and adipose tissue inflammation in mice treated with high fat diet (HFD) after chronic treatment with VU0409106. Furthermore, a negative modulation of mGluR5 also reduces binge-like eating, the most common type of eating disorder. Altogether, our results pointed out mGluR5 as a potential target for treating obesity, as well as related disorders.